Analysis of Transformational Leadership Indicators of School Principals As Leaders of 21st Century Technology Implementation - Noviyanti, Rani (PT. Hafasy Dwi Nawasena, 2024)
In the modern era which is full of competition and challenges, one phenomenal leadership style is offered, namely the transformational leadership style. This transformational leadership style is believed to be able to bring an organization to develop in a positive direction without ignoring the interests of its followers. Schools are no exception. Many schools today, both private and public, realize the importance of the role of a principal and implement this transformational leadership style in schools. The research was carried out using the Systematic Literature Review (SLR) method, namely by first collecting study materials related to obstacles in decision making and related to decision making itself in the form of books, articles and other sources. After the study material is collected, the material is then researched and studied, then the author tries to conclude new knowledge as a result of the analysis of the study material. Based on the research results, 4 factors were obtained to measure the transformational leadership of school principals, namely: 1) Idealized influence: 2) Inspirational motivation: 3) Intellectual stimulation: 4) Individualized consideration (individual attention) . It is hoped that strengthening the transformational leadership of school principals can optimize teachers' innovative behavior which can improve the quality of education.